The Use of Audio-Visual Media in Increasing Students' Motivation to Learn Islamic Religious Education - Arisman; Usman; D, Muh. Akib; Kamaruddin; Jufri, Muhammad (Jurnal Amal Pendidikan, 2024)
This study examines the use of audio-visual media in enhancing students' motivation to learn Islamic Religious Education (IRE) at UPTD SMPN 5 Barru. Education plays a crucial role in shaping individuals' cognitive and character development, with innovative teaching methods being essential to improve engagement and outcomes. The research employs a qualitative, descriptive approach, collecting data through interviews and observations to explore the impact of audio-visual media on motivation and learning. The findings reveal that audio-visual media, such as videos, significantly increases students' interest and comprehension of IRE topics, fostering creativity, confidence, and active participation. Supporting factors include the availability of facilities, teacher skills, and parental involvement, while barriers include limited technological resources and variability in students' abilities. The study concludes that audio-visual media effectively addresses learning challenges, enhances student focus, and improves academic performance, though its optimal use requires teacher expertise and sufficient resources.